Analisis "Moment Of Truth" di Sanya International Shopping Center Hainan sebagai atraksi wisata belanja - Mbulu, Yustisia Pasfatima; Putri, Shinta karissa; Khawarizmi, Maharanti; Ramadhani, Fitria Nur; Aghnia, Putri Nazwa; Ferdy, Adrian Matthew (Journal of Indonesian Tourism, Hospitality and Recreation, 2025)
AbstractThis study focuses on the experience of Indonesian tourists in shopping tourism at Sanya International Shopping Center, Hainan, China, using the Moment of Truth (MOT) theory. This study analyzes the stages of the Moment of Truth (MOT) in Indonesian tourists visiting the Sanya International Shopping Center in Hainan Province, China. This study uses a qualitative descriptive method with data obtained through direct interviews with informants and observations and secondary data from related documents. The results of this discussion indicate that the process of the Moment Of Truth stages of Indonesian tourists visiting the Sanya International Shopping Center Mall has been fully implemented. This stage takes place from the Zero Moment Of Truth stage, continues to the First Moment Of Truth stage, the Second Moment Of Truth, and finally the Ultimate Moment Of Truth. This stage ends with tourists providing reviews, responses, and recommendations to other users based on their experiences on Google Reviews, which will influence other potential visitors.AbstrakPenelitian ini berfokus pada pengalaman wisatawan Indonesia dalam melakukan wisata belanja di Sanya International Shopping Center, Hainan China dengan penggunaan teori Moment of Truth (MOT). Penelitian ini bertujuan untuk menganalisis tahapan Moment of Truth (MOT) pada wisatawan Indonesia yang berkunjung ke Sanya International Shopping Center yang terletak di provinsi Hainan, China. Penelitian ini menggunakan metode deskriptif kualitatif dengan data yang diperoleh melalui wawancara secara langsung dengan narasumber dan observasi, serta data sekunder dari dokumen terkait. Hasil pembahasan ini menunjukan bahwa proses dari tahapan Moment Of Truth wisatawan Indonesia yang berkunjung ke Mall Sanya International Shopping Center sudah terlaksana sepenuhnya. Tahapan ini berlangsung dari tahapan  Zero Moment Of Truth, dilanjutkan ketahapan First Moment Of Truth, Second Moment Of Truth, dan terakhir Ultimate Moment Of Truth. Tahapan ini diakhiri dengan wisatawan memberikan ulasan, tanggapan, dan juga rekomendasi kepada pengguna lain berdasarkan pengalaman di google review, yang akan mempengaruhi calon pengunjung lainnya.